Buscas adolescentes e aconselhamento pastoral à luz da logoterapia - Sousa Filho, Vicente Gregório de (2011)
With so many changes and concerns raised by the so-called postmodern , many senses of values and socio-cultural determinations in crisis before the interpellation marked by neoliberal notion of commodity. The new technologies also promoted new views and perspectives that generate a new way of dealing with subjectivity. Thus, this work seeks to understand how is the search for meaning among adolescents from the notion of Logotherapy, articulated by Viktor Frankl, and as the approach to counseling can to help in the search for existential referrals. We will discuss the logotherapeutic concepts in order to aid the process of pastoral counseling of adolescents and guide toward a reasonable insights of vocational guidance.